EFFECTS OF RADIOPROTECTIVE PROPERTIES OF A CONCENTRATE OF POLYPHENOLS FROM GRAPE CABERNET SAUVIGNON IN THE KAZAKHSTAN REGION ON RADIATION SICKNESS IN RATS - Sergazy , S.S.; Shulgau , Z.T.; Gulyayev , A.E.; Kabdulina , A.A.; Nurgozhin , T.S. (Eurasian Journal of Applied Biotechnology, 2015)
Acute radiation syndrome (ARS) is one of the major problems in treating cancer patients using radiation therapy. ARS is caused by the death of rapidly dividing cells with short-term radiation. There is a strong correlation between ARS and the dose of ionizing radiation received by patients. Here, we describe the effect of a polyphenol concentrate of Cabernet Sauvignon grapes obtained from the Kazakhstan region on radiation sickness in rats. Acute radiation sickness in rats was induced by a single exposure to radiation at a dose of 8 Gray (Gy) by using a Rocus-AM equipment. The occurrence of radiation sickness was monitored by haematological analysis of blood collected from the tail vein of the rats one week after irradiation. The animals received a concentrate of polyphenols from grapes in therapeutic (after exposure) and prophylactic (one week before irradiation) forms. The oxidative status of rat plasma, measured as the amount of free radicals and the total antioxidant activity, was examined. The results demonstrate that a concentrate of grape polyphenols has radioprotective properties due to the observed increase in total plasma antioxidant activity. In addition, the polyphenols concentrate limited the development of pancytopenia.